Spherical-like ZSM-48 molecular sieve, preparation method and application thereof, and n-heptane hydroisomerization method

By preparing spherical ZSM-48 molecular sieve formed by nanoparticles and undergoing hydrogen modification, the problem of poor catalytic performance of existing ZSM-48 is solved, the catalytic performance and molecular diffusion are improved, and the efficiency of n-heptane iso-efficient Structural reaction.

CN119160915AActive Publication Date: 2024-12-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310714492.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-20
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

The existing ZSM-48 molecular sieve has poor catalytic performance, and the pore structure is not conducive to molecular diffusion, resulting in low catalyst utilization and reduced product selectivity.

Method used

The mixed liquid formed by silicon-containing source, quaternary ammonium-type cationic polymer, alkaline source and aluminum source raw materials were crystallized to prepare spherical ZSM-48 molecular sieve formed by agglomeration of nanoparticles, and after hydrogen modification, it is used as a The catalyst is subjected to a hydroisomerization reaction of n-heptane.

Benefits of technology

The spherical ZSM-48 molecular sieve that realizes the agglomeration of nanoparticles has a wide range of silicon-aluminum ratios and adjustable acid properties, which improves catalytic performance and molecular diffusion properties, and can efficiently carry out the isomerization reaction of n-heptane to obtain High yield single-branch and double-branch isomer products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160915A_ABST
    Figure CN119160915A_ABST
Patent Text Reader

Abstract

The invention relates to the field of molecular sieves, and discloses a spheroidic ZSM-48 molecular sieve, a preparation method and application thereof, and an n-heptane hydroisomerization method. The molecular sieve has a sphere-like aggregate morphology agglomerated by nano-particle crystals, the length of the nano-particle crystals is 20-50nm, and the width of the nano-particle crystals is 8-40nm. The ZSM-48 molecular sieve provided by the invention has a sphere-like morphology formed by agglomeration of nanoparticles, also has a wide silica-alumina ratio range and adjustable acid properties, is good in accessibility, can be used as an adsorbent or a catalyst for conversion of organic compounds, and has good catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molecular sieves, and in particular to a quasi-spherical ZSM-48 molecular sieve and a preparation method and application thereof, and a method for hydroisomerizing n-heptane. Background Art

[0002] Molecular sieves are a type of inorganic microporous crystalline material with high specific surface area, controllable pore structure and skeleton composition, and excellent hydrothermal stability. They are widely used in petrochemicals, coal chemical industry, industrial separation processes, and ion exchange. Common industrial molecular sieves are often micron-sized, and their pores are in the micropore (<2nm) range. Therefore, the diffusion and mass transfer of molecules in the micropores are slow, which easily leads to mass transfer resistance. When used as a catalyst, the slow diffusion and mass transfer rate of molecules in the molecular sieve can easily lead to reduced catalyst utilization, the product is prone to side reactions and reduced selectivity, and the catalyst is prone to carbon deposition and deactivation. Nanosheet molecular sieves can solve the above-mentioned mass transfer difficulties and a series of problems caused by inaccessible acid sites due to their larger specific surface area, shorter pores and more exposed acid sites.

[0003] ZSM-48 molecular sieve has a one-dimensional 10-membered ring channel with a *MRE topological structure. The structural directing agents commonly used to synthesize ZSM-48 molecular sieves include 1,6-hexanediamine (HDA), hexamethylammonium bromide (HMBr2), etc., which are easy to produce competing phases such as EUO, MWW or MTW during the synthesis process, and the silicon-aluminum ratio of the synthesized ZSM-48 sample is usually higher than 100, resulting in a low acid density, which limits its catalytic application. Hong et al. successfully synthesized a ZSM-48 molecular sieve with a low silicon-aluminum ratio (Si / Al=30) using pentamethylammonium bromide (PMBr2) as a structural directing agent, but the B acid density is low, which is not conducive to catalytic application [Suk Bong Hong et al., Microporous and Mesoporous Materials, 2004, 68, 97-104]. In addition, the molecular sieve crystals in ZSM-48 synthesized by the above method usually grow into needle-shaped or rod-shaped structures along the one-dimensional channel direction, but their catalytic performance is poor. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem of poor catalytic performance of ZSM-48 in the prior art, and to provide a quasi-spherical ZSM-48 molecular sieve and its preparation method and application, and a method for hydroisomerization of n-heptane. The ZSM-48 molecular sieve can be used as an adsorbent or a catalyst for conversion of organic compounds.

[0005] The first aspect of the present invention provides a quasi-spherical ZSM-48 molecular sieve, wherein the molecular sieve has a quasi-spherical aggregate morphology formed by agglomeration of nanoparticle crystals, and the length of the nanoparticle crystals is 20-50nm and the width is 8-40nm.

[0006] The second aspect of the present invention provides a method for preparing the ZSM-48 molecular sieve described in the first aspect of the present invention, wherein the preparation method comprises:

[0007] A mixed solution formed by raw materials containing silicon source, quaternary ammonium cationic polymer, alkali source and aluminum source is crystallized;

[0008] Wherein, the quaternary ammonium cationic polymer is composed of the structural unit a shown in formula (I),

[0009]

[0010] In formula (I), p and q are each independently an integer between 2 and 4, R1 and R2 are each independently a methyl group or an ethyl group, and X is a halogen or OH.

[0011] The third aspect of the present invention provides the use of the ZSM-48 molecular sieve described in the first aspect of the present invention in adsorption treatment and / or organic compound conversion reaction.

[0012] The fourth aspect of the present invention provides a method for the hydroisomerization of n-heptane, wherein the method comprises: using the ZSM-48 molecular sieve described in the first aspect of the present invention and / or the hydrogen-type ZSM-48 molecular sieve obtained by hydrogen-modification of the ZSM-48 molecular sieve described in the first aspect of the present invention as a catalyst and in the presence of hydrogen, n-heptane isomerized.

[0013] Through the above technical scheme, the ZSM-48 molecular sieve of the present invention has a spherical morphology formed by agglomeration of nanoparticles, and has a wide silicon-aluminum ratio range and adjustable acid properties, good accessibility, can be used as an adsorbent or a catalyst for organic compound conversion, and has good catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is the X-ray diffraction pattern of the molecular sieve sample in Example 1;

[0015] Figure 2 is a SEM image of the molecular sieve sample in Example 1 at a magnification of 10,000;

[0016] Figure 3 is a SEM image of the molecular sieve sample in Example 1 at a magnification of 20,000;

[0017] Figure 4 is the X-ray diffraction pattern of the molecular sieve sample in Example 4;

[0018] Figure 5 is a SEM image of the molecular sieve sample in Example 4 at a magnification of 10,000;

[0019] Figure 6 is a SEM image of the molecular sieve sample in Example 4 at 40,000 magnification;

[0020] Figure 7 is the X-ray diffraction pattern of the molecular sieve sample in Example 6;

[0021] Figure 8 is a SEM image of the molecular sieve sample in Example 6 at 40,000 magnification;

[0022] Fig. 9 This is a SEM image of the molecular sieve sample in Example 6 at 80,000 magnification;

[0023] Fig.10 This is the SEM image of the molecular sieve sample in Comparative Example 1. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] In the present invention, the quasi-spherical ZSM-48 molecular sieve refers to the ZSM-48 molecular sieve having an aggregate shape that is approximately spherical, and / or having some tiny defects on the surface of the spherical aggregate.

[0026] The first aspect of the present invention provides a spherical ZSM-48 molecular sieve, wherein the molecular sieve has a spherical aggregate morphology formed by agglomeration of nanoparticle crystals; the length of the nanoparticle crystals is 20-50nm and the width is 8-40nm.

[0027] The ZSM-48 molecular sieve in the present invention has a spherical aggregate morphology formed by nanoparticles agglomerating, and the nanoparticles are in close contact when agglomerated. The spherical aggregates formed by nanoparticles of specific length and width make the molecular sieve have good molecular diffusion and adsorption properties. The molecular sieve has good accessibility when used and has good catalytic performance in organic matter conversion reactions.

[0028] In the present invention, whether the structure of the molecular sieve is ZSM-48 molecular sieve is determined by X-ray diffraction spectrum (XRD), and the X-ray diffraction spectrum (XRD) is determined by X-ray powder diffractometer. Before determining the structure of the molecular sieve, a scanning electron microscope (SEM) is used to observe the crystallization of the molecular sieve sample to confirm that the sample contains only one crystal, that is, the molecular sieve sample is a pure phase. On this basis, an XRD test is performed to ensure that there are no interference peaks of other crystals in the diffraction peaks in the XRD spectrum. The X-ray diffraction spectrum (XRD) is determined by an X-ray powder diffractometer (model D / MAX 2550VB / PC of Rigaku Company of Japan, which analyzes the physical phase of the sample, and a CuKα ray source is used. Nickel filter, 2θ scanning range 5-50°, operating voltage 40KV, current 40mA, scanning rate 10° / min).

[0029] According to the present invention, in some preferred embodiments, the length of the nanoparticle crystal is 25-50 nm, for example, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm. The molecular sieve under the above embodiment has better adsorption and catalytic properties when used.

[0030] According to the present invention, in some preferred embodiments, the width of the nanoparticle crystal is 10-35nm, for example, 10nm, 12nm, 13nm, 15nm, 18nm, 20nm, 22nm, 25nm, 30nm or 35nm. The molecular sieve under the above embodiment has excellent use effect when used as an adsorbent or a catalyst for organic compound conversion.

[0031] According to the present invention, in some preferred embodiments, the size of the agglomerates is 2-10 μm, for example, 2 μm, 2.5 μm, 2.8 μm, 3.5 μm, 4.1 μm, 6 μm, 7 μm, 7.5 μm, 7.8 μm, 7.9 μm, 8.5 μm or 9 μm, preferably 2.5-9 μm. The molecular sieve under the above embodiment has a short axis structure, small resistance to molecules, good diffusivity and catalytic properties.

[0032] According to the present invention, in some preferred embodiments, the aspect ratio of the nanoparticle crystal is 1.2-5, for example, 1.2, 1.3, 1.5, 2, 2.8, 3, 3.1, 3.5, 3.8, 4, 4.5 or 5, preferably 1.3-4.5. The molecular sieve under the aforementioned embodiment has good accessibility and has good catalytic performance for organic conversion reaction.

[0033] In the present invention, the morphology of ZSM-48 molecular sieve is observed by scanning electron microscope (SEM, model is NOVA Nano SEM 450 field emission scanning electron microscope of FEI Company of the United States), the molecular sieve is observed under a certain magnification by using the scanning electron microscope, an observation field of view is randomly selected, the average value of the length and width of all nanoparticles in the observation field of view is calculated, the operation is repeated for a total of 10 times, and the average value of the sum of 10 times is taken as the length and width of the nanoparticle crystal, the size of all agglomerates in the observation field of view is measured by the same method, and the operation is repeated 5 times; and the nanoparticle crystal is located in a three-dimensional crystal, and its maximum outer diameter is the length of the nanoparticle crystal, the maximum diameter in the cross section with the largest area in the cross section perpendicular to the length is set as the width, and the minimum diameter is the thickness. In the present invention, only the length and width that are relatively larger than the thickness are described, and the thickness is not excessively restricted.

[0034] According to the present invention, the molecular sieve of the specific morphology of the present invention has a certain pore volume. In some embodiments, the total pore volume of the molecular sieve is not less than 0.2 cm 3 / g. The molecular sieve of the aforementioned embodiment has good adsorption and diffusion properties.

[0035] According to the present invention, in some preferred embodiments, the total pore volume of the molecular sieve is 0.2-0.6 cm 3 / g, for example 0.2 cm 3 / g, 0.25 cm 3 / g, 0.3 cm 3 / g, 0.35 cm 3 / g, 0.36 cm 3 / g, 0.37 cm 3 / g, 0.38 cm 3 / g, 0.39 cm 3 / g, 0.4 cm 3 / g, 0.5 cm 3 / g or 0.6 cm 3 / g. The molecular sieve of the above embodiment has good adsorption and diffusivity, and has good catalytic performance when used in organic matter conversion reactions.

[0036] According to the present invention, the molecular sieve of the specific morphology of the present invention has certain micropores. In some embodiments, the micropore volume of the molecular sieve is not less than 0.05 cm 3 / g. The molecular sieve of the aforementioned embodiment has good adsorption and diffusion properties.

[0037] According to the present invention, in some preferred embodiments, the micropore volume of the molecular sieve is 0.05-0.15 cm 3 / g, for example 0.05 cm 3 / g, 0.06 cm 3 / g, 0.07 cm 3 / g, 0.08 cm 3 / g, 0.09 cm 3 / g, 0.1 cm 3 / g, 0.12 cm 3 / g or 0.15 cm 3 / g. The molecular sieve of the above embodiment has good adsorption and diffusivity, and has good catalytic performance when used in organic matter conversion reactions.

[0038] According to the present invention, the molecules of the specific morphology of the present invention have a high specific surface area. In some embodiments, the total specific surface area of ​​the molecular sieve is not less than 300 m 2 / g. The molecular sieve of the aforementioned embodiment has good accessibility and has good catalytic performance in organic matter conversion reactions.

[0039] According to the present invention, in some preferred embodiments, the total specific surface area of ​​the molecular sieve is 300-450 m 2 / g, for example 300 m 2 / g, 310m 2 / g, 319m 2 / g, 329m 2 / g, 331m 2 / g, 334m 2 / g, 336m 2 / g, 341m 2 / g, 345m 2 / g, 352m 2 / g, 360m 2 / g, 370m 2 / g, 370m 2 / g, 400m 2 / g, 420m 2 / g or 450m 2 / g. The molecular sieves used in the above implementations have good catalytic performance in organic matter conversion reactions.

[0040] According to the present invention, in some embodiments, the external specific surface area of ​​the molecular sieve is not less than 100 m 2 / g. The molecular sieve of the aforementioned embodiment has good catalytic performance in organic matter conversion reaction.

[0041] According to the present invention, in some preferred embodiments, the external specific surface area of ​​the molecular sieve is 100-200 m 2 / g, for example, 100 m 2 / g, 120m 2 / g, 130m2 / g, 149m 2 / g, 154m 2 / g, 156m 2 / g, 157m 2 / g, 161m 2 / g, 166m 2 / g, 172m 2 / g, 178m 2 / g, 185m 2 / g, 195m 2 / g or 200m 2 / g. The molecular sieves used in the above-mentioned implementations have good catalytic performance in organic matter conversion reactions.

[0042] In the present invention, the total pore volume, micropore volume, total specific surface area and external specific surface area of ​​the molecular sieve are measured by nitrogen physical adsorption and desorption method (BET method), and the nitrogen physical adsorption and desorption isotherm of the molecular sieve is measured by physical adsorption instrument (Beishide Instrument Technology (Beijing) Co., Ltd. 3H-2000PS4 model), and then calculated by BET equation and t-plot equation. The experimental conditions for the molecular sieve are: measurement temperature -196 ° C, before measurement, the molecular sieve is first heat-treated at 550 ° C in air atmosphere for 6 hours, and then vacuum-pretreated at 350 ° C for 4 hours.

[0043] According to the present invention, the molecular sieve of the specific morphology of the present invention has a wide range of silicon-aluminum ratios. In some embodiments, the SiO2 / Al2O3 molar ratio of the molecular sieve is 40-350, for example, 40, 50, 57, 60, 75, 105, 116, 191, 200, 246, 300 or 350, preferably 50-300. The molecular sieve of the aforementioned embodiment has a wide range of silicon-aluminum ratios, and the acid properties are adjustable, the accessibility is good, and the use thereof for organic conversion reactions has good catalytic performance.

[0044] In the present invention, the SiO2 / Al2O3 molar ratio of the molecular sieve is measured by an inductively coupled plasma atomic emission spectrometer (ICP) model Varian 710-ES, and the analysis sample is dissolved with hydrofluoric acid to obtain the element content.

[0045] The second aspect of the present invention provides a method for preparing the ZSM-48 molecular sieve described in the first aspect of the present invention, wherein the preparation method comprises:

[0046] A mixed solution formed by raw materials containing silicon source, quaternary ammonium cationic polymer, alkali source and aluminum source is crystallized;

[0047] Wherein, the quaternary ammonium cationic polymer is composed of the structural unit a shown in formula (I),

[0048]

[0049] In formula (I), p and q are each independently an integer between 2 and 4, R1 and R2 are each independently a methyl group or an ethyl group, and X is a halogen or OH.

[0050] In the present invention, halogens that can be mentioned are fluorine, chlorine, bromine and iodine.

[0051] In the present invention, the quaternary ammonium cationic polymer is formed by repeatedly connecting the same structural unit a. It can be understood by those skilled in the art that the polymer product obtained by the polymerization reaction generally exists in the form of a mixture, and the number of monomers contained in the molecular chain of each polymer is different, that is, a mixture of polymers with different polymerization degrees. In some embodiments, the average polymerization degree of the quaternary ammonium cationic polymer is 2-20, preferably 3-13. That is, the average polymerization degree described in the present invention refers to the average number of structural units a contained in the quaternary ammonium cationic polymer.

[0052] According to the present invention, R1 and R2 may be the same or different. Based on the consideration of the availability of raw materials, in some embodiments, in formula (I), R1 and R2 are the same.

[0053] According to the present invention, in some preferred embodiments, the quaternary ammonium cationic polymer is selected from one or more of the quaternary ammonium cationic polymer A1 composed of the structural unit a1, the quaternary ammonium cationic polymer A2 composed of the structural unit a2, the quaternary ammonium cationic polymer A3 composed of the structural unit a3 and the quaternary ammonium cationic polymer A4 composed of the structural unit a4, wherein: in the structural unit a1, p is 4, q is 3, R1 and R2 are methyl; in the structural unit a2, p is 4, q is 3, R1 and R2 are ethyl; in the structural unit a3, p is 4, q is 4, R1 and R2 are methyl; in the structural unit a4, p is 4, q is 4, R1 and R2 are ethyl. The molecular sieve obtained by the above-mentioned embodiment has good diffusivity and adsorption.

[0054] According to the present invention, as long as the purpose of the present invention can be achieved, there is no special restriction on the amount of raw materials used in preparing the molecular sieve. In some embodiments, the silicon source is calculated as SiO2, and the quaternary ammonium cationic polymer is calculated as structural unit a, and the molar ratio of the silicon source to the quaternary ammonium cationic polymer is 1: (0.1-0.4), such as 1: 0.1, 1: 0.15, 1: 0.2, 1: 0.33, 1: 0.35 or 1: 0.4, preferably 1: (0.1-0.35). The molecular sieve obtained in the above embodiment has a special morphology that is conducive to molecular diffusion.

[0055] According to the present invention, it can be understood that the quaternary ammonium cationic polymer, calculated as structural unit a, refers to the total amount of structural unit a contained in the reaction raw material system.

[0056] According to the present invention, in some embodiments, the silicon source is SiO2 and the alkali source is cation, and the molar ratio of the silicon source to the alkali source is 1:(0.15-0.5), preferably 1:(0.2-0.45). The above embodiment is conducive to the crystallization process and better forms the molecular sieve of the special morphology of the present invention.

[0057] In the present invention, it can be understood that the mixed solution formed by the raw materials containing silicon source, quaternary ammonium cationic polymer, alkali source and aluminum source refers to the mixed solution obtained by mixing the raw materials (including silicon source, quaternary ammonium cationic polymer, alkali source and aluminum source) in the presence of a solvent, wherein the solvent can be selected as needed, such as water; as long as it can be mixed evenly, the mixing method is not particularly limited, such as stirring at room temperature (referring to 20-30°C) for 12-36 hours.

[0058] According to the present invention, in some embodiments, the silicon source is calculated as SiO2, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of the silicon source to the aluminum source is 1: (0-0.025), and is not 0, preferably 1: (0-0.02), and is not 0. The above embodiment can obtain a molecular sieve with a wide silicon-to-aluminum ratio, and the molecular sieve has good accessibility.

[0059] According to the present invention, in some embodiments, the silicon source is calculated as SiO2, and the molar ratio of the silicon source to the solvent in the mixed solution is 1:(10-100), preferably 1:(12-90). The above embodiments enable the crystallization process to be performed better.

[0060] According to the present invention, those skilled in the art will understand that the silicon source is a raw material for providing silicon elements in the molecular sieve. As long as the purpose of the present invention can be achieved, the type of the silicon source is not particularly limited. In some embodiments, the silicon source is selected from one or more of tetraethyl orthosilicate, fumed silica, silica sol and white carbon black.

[0061] According to the present invention, those skilled in the art will understand that the alkali source is a raw material for providing alkali metals in molecular sieves. As long as the purpose of the present invention can be achieved, the type of the alkali source is not particularly limited. In some embodiments, the alkali source is selected from one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide.

[0062] According to the present invention, those skilled in the art will understand that the aluminum source is a raw material for providing the aluminum element in the molecular sieve. As long as the purpose of the present invention can be achieved, the type of the aluminum source is not particularly limited. In some embodiments, the aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, sodium aluminate, pseudo-boehmite and aluminum isopropoxide.

[0063] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the crystallization treatment are not particularly limited. In some embodiments, the conditions of the crystallization treatment include: a crystallization temperature of 30-190°C, for example, 30°C, 50°C, 100°C, 140°C, 160°C, 170°C, 180°C or 190°C, preferably 140-180. The above embodiment can better obtain a molecular sieve with a spherical aggregate morphology formed by agglomeration of nanoparticle crystals.

[0064] According to the present invention, in some preferred embodiments, the conditions of the crystallization treatment include: the crystallization time is 2-12 days, such as 2 days, 3 days, 4 days, 7 days, 9 days, 10 days or 12 days, preferably 3-10 days. The above-mentioned embodiment can better ensure the progress of the crystallization treatment, and the molecular sieve with a specific morphology has better catalytic performance.

[0065] According to the present invention, in some embodiments, the preparation method further comprises: performing solid-liquid separation and heat treatment after the crystallization treatment.

[0066] According to the present invention, solid-liquid separation is to separate solid matter from the material obtained by crystallization treatment. During the solid-liquid separation process, washing can be performed as needed, wherein water and / or ethanol can be used for washing.

[0067] According to the present invention, the purpose of heat treatment is to remove substances such as solvents and templates in the solid obtained by solid-liquid separation. In some embodiments, the conditions of heat treatment include calcination after drying.

[0068] According to the present invention, there is no particular limitation on the drying conditions, and the drying can be carried out using conventional drying methods in the art, such as drying at 40-250°C, preferably at 60-150°C for 8-30 hours, preferably 10-20 hours; wherein, the drying can be carried out under normal pressure or under reduced pressure.

[0069] According to the present invention, in some preferred embodiments, the calcination conditions include: a calcination temperature of 300-800°C, preferably 400-650°C.

[0070] According to the present invention, in some preferred embodiments, the calcination conditions include: the calcination time is 1-10 hours, preferably 3-6 hours.

[0071] According to the present invention, in some preferred embodiments, the calcination conditions include: calcination is carried out in an oxygen-containing atmosphere, wherein the oxygen-containing atmosphere may be air or oxygen.

[0072] The third aspect of the present invention provides the use of the ZSM-48 molecular sieve described in the first aspect of the present invention in adsorption treatment and / or organic compound conversion reaction.

[0073] In the present invention, the ZSM-48 molecular sieve with a specific morphology can better adsorb organic molecules, such as adsorption utilization in organic waste gas treatment; and the ZSM-48 molecular sieve with a specific morphology also has good molecular diffusion, and has good catalysis and stability when used in organic compound conversion reactions.

[0074] In the present invention, as required, the ZSM-48 molecular sieve can be used directly or after being modified by conventional methods in the art. In some embodiments, the ZSM-48 molecular sieve is directly used as an active component and / or the hydrogen-type ZSM-48 molecular sieve obtained by hydrogen modification of the ZSM-48 molecular sieve is used as an active component.

[0075] In the present invention, those skilled in the art can select the hydrogen-modified ZSM-48 molecular sieve or the unmodified ZSM-48 molecular sieve for use according to practical applications, or can select the hydrogen-modified ZSM-48 molecular sieve and the unmodified ZSM-48 molecular sieve for use in combination.

[0076] In the present invention, the hydrogen modification of ZSM-48 molecular sieve is a conventional modification method in the art, that is, the ZSM-48 molecular sieve is ammonium exchanged by an ammonium salt aqueous solution, and then centrifugal washing, drying, and calcination are performed to prepare the hydrogen ZSM-48 molecular sieve; wherein, the number of ammonium exchange and centrifugal washing can be selected as needed, and the methods and conditions of ammonium exchange, centrifugal washing, drying and calcination are conventional methods in the art. In the present invention, the advantages of the present invention are illustrated by taking the following hydrogen modification method as an example, but the present invention is not limited thereto:

[0077] The ZSM-48 molecular sieve was subjected to ammonium ion exchange at 65°C for 3 hours, then centrifuged and washed, and the above steps were repeated twice. After that, it was dried at 100°C overnight (8-12 hours) and then calcined in air at 550°C for 4 hours to obtain the hydrogen-type ZSM-48 molecular sieve.

[0078] In the present invention, ammonium exchange is to use ammonium ions to exchange the alkali metal atoms connected to the O adjacent to Al in the ZSM-48 molecular sieve framework with NH4 ions in the solution, so as to convert the ZSM-48 molecular sieve into NH4 type ZSM-48, and then finally convert it into hydrogen type ZSM-48 molecular sieve by methods including calcination. It can be understood by those skilled in the art that the hydrogen type ZSM-48 molecular sieve obtained after ammonium exchange and calcination is only a change in the amount of acid, and the specific surface area, pore volume, SiO2 / Al2O3 molar ratio, structure and crystal structure morphology and other characteristics of the hydrogen type ZSM-48 molecular sieve are the same as those without ammonium exchange and calcination treatment.

[0079] According to the present invention, in some embodiments, the total acid content of the hydrogen ZSM-48 molecular sieve is not higher than 1000 μmol / g. The molecular sieve of the aforementioned embodiment has good catalytic performance in organic matter conversion reaction.

[0080] According to the present invention, in some preferred embodiments, the total acid amount of the hydrogen ZSM-48 molecular sieve is 50-1000 μmol / g, for example, 50 μmol / g, 100 μmol / g, 294 μmol / g, 357 μmol / g, 476 μmol / g, 493 μmol / g, 579 μmol / g, 621 μmol / g, 633 μmol / g, 645 μmol / g, 691 μmol / g, 750 μmol / g, 850 μmol / g, 950 μmol / g or 1000 μmol / g. The molecular sieve of the aforementioned embodiment has good catalytic performance.

[0081] According to the present invention, in some embodiments, the strong acid content of the hydrogen ZSM-48 molecular sieve is not higher than 400 μmol / g. The molecular sieve of the aforementioned embodiment has good catalytic performance, and when used in organic matter conversion reactions, the target product has a high yield.

[0082] According to the present invention, in some preferred embodiments, the strong acid amount of the hydrogen ZSM-48 molecular sieve is 20-400 μmol / g, for example, 20 μmol / g, 79 μmol / g, 123 μmol / g, 172 μmol / g, 192 μmol / g, 209 μmol / g, 224 μmol / g, 230 μmol / g, 300 μmol / g, 350 μmol / g or 400 μmol / g. When the molecular sieve of the aforementioned embodiment is used for organic matter conversion reaction, the target product has a high yield.

[0083] In the present invention, the total acid content and strong acid content of hydrogen-type ZSM-48 molecular sieve are measured by NH3-TPD chemical adsorption-desorption curve using Micrometer Chemisorb 2720 instrument. Before the test, the sample is activated at 550°C for 1h, ammonia is adsorbed at 100°C for 20min, and then desorption is detected at 100-600°C. The peak area is quantified by quantitative ring pulse ammonia, and the peak is separated by Gaussian distribution. The acid content corresponding to the desorption temperature above 300°C can be considered as the strong acid content.

[0084] In the present invention, ZSM-48 molecular sieve directly used as active component or hydrogen-type ZSM-48 molecular sieve used as active component means that the corresponding molecular sieve can be directly used as catalyst according to needs, or the molecular sieve and adhesive can be prepared into strip or clover-shaped molded products as catalysts according to needs, or the molecular sieve can be prepared into corresponding catalyst products according to other means in the art, and the present invention has no special restrictions on this.

[0085] According to the present invention, the organic compound conversion reactions involved include various types of carbon-carbon bond breakage and recombination and / or carbon-hydrogen bond breakage and recombination reactions. In some embodiments, the organic compound conversion reactions include isomerization reactions, hydrogenation isomerization reactions, and hydrogenolysis reactions. The molecular sieve of the special morphology of the present invention has good accessibility and has good catalytic properties in the reactions used in the aforementioned embodiments.

[0086] The fourth aspect of the present invention provides a method for the hydroisomerization of n-heptane, wherein the method comprises: using the ZSM-48 molecular sieve described in the first aspect of the present invention and / or the hydrogen-type ZSM-48 molecular sieve obtained by hydrogen-modification of the ZSM-48 molecular sieve described in the first aspect of the present invention as a catalyst and in the presence of hydrogen, n-heptane isomerized.

[0087] In the present invention, when the ZSM-48 molecular sieve with special morphology or the hydrogen-type ZSM-48 molecular sieve obtained after its modification is used for the hydroisomerization of n-heptane, it not only has good catalytic performance, but also can obtain high-yield single-branched alkane and double-branched alkane isomer products.

[0088] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the isomerization reaction are not particularly limited. In some embodiments, the conditions of the isomerization reaction include: a mass space velocity of 0.5-3.5h -1 .

[0089] According to the present invention, in some embodiments, the conditions of the isomerization reaction include: the reaction temperature is 200-400°C.

[0090] According to the present invention, in some embodiments, the molar ratio of hydrogen to n-heptane is 10-40.

[0091] The present invention will be described in detail below by way of examples. In the following examples:

[0092] The quaternary ammonium cationic polymer (SDA) is composed of the structural unit a shown in formula (I):

[0093]

[0094] In the following examples and comparative examples, the prepared molecular sieves were subjected to hydrogen modification to obtain hydrogen-type molecular sieves. The method of hydrogen modification was as follows: the molecular sieves were subjected to ammonium ion exchange at 65°C for 3 hours, and then centrifuged and washed, and the above steps were repeated twice, and then dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain hydrogen-type molecular sieves;

[0095] The hydrogen molecular sieve is used as a catalyst in the hydroisomerization reaction of n-heptane, and the conditions of the isomerization reaction are: the catalyst loading is 0.4 g, the particle size is 20-40 mesh, the molar ratio of hydrogen to n-heptane is 26, the reaction temperature is 200-400°C, and the mass space velocity is 1h -1 The highest yield of the isomer product obtained as the reaction time is measured is the isomer yield.

[0096] Yield of isomers % = (mass of isomers in the product) / (total mass of carbon-containing products) × 100%;

[0097] The isomer products are single-branched alkanes and double-branched alkane isomers, and the carbon-containing by-products are mainly cracking products, wherein the raw material n-heptane is not included in the products.

[0098] Example 1

[0099] 4.30 g of deionized water, 0.48 g of SDA (p is 4, q is 3, R1 and R2 are methyl, X is Br, and the average degree of polymerization is 3.1), 0.045 g of aluminum nitrate nonahydrate, 0.08 g of sodium hydroxide, and 1.27 g of tetraethyl orthosilicate were stirred at room temperature for 24 hours to prepare a mixture;

[0100] The mixture was placed in a stainless steel reactor and crystallized at 180°C for 7 days. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0101] Figure 1 is the X-ray diffraction diagram of the molecular sieve sample, and it can be concluded that the molecular sieve sample is ZSM-48 molecular sieve;

[0102] Figure 2 and Figure 3 The SEM images of the molecular sieve sample at 10,000 times and 20,000 times respectively show that the morphology of the molecular sieve sample is a spherical agglomerate formed by the aggregation of nanoparticle crystals. The length of the nanoparticle crystal is 45nm, the width is 15nm, the aspect ratio is 3, and the size of the agglomerate is 7.5μm.

[0103] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) and was found to be 91;

[0104] The total specific surface area of ​​the molecular sieve sample is 345 m 2 / g, external specific surface area 156 m 2 / g, total pore volume 0.39 cm 3 / g, micropore volume is 0.06 cm 3 / gram;

[0105] The prepared molecular sieve sample was hydrogen-modified to obtain hydrogen-type ZSM-48 molecular sieve. The total acid content of the ZSM-48 molecular sieve sample was 493 μmol / g, the strong acid content was 149 μmol / g, and the strong acid content accounted for 30% of the total acid content.

[0106] The hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches a maximum of 70%.

[0107] Example 2

[0108] 5.40 g of deionized water, 0.60 g of SDA (p is 4, q is 3, R1 and R2 are methyl, X is Br, and the average degree of polymerization is 3.1), 0.09 g of aluminum nitrate nonahydrate, 0.09 g of sodium hydroxide, and 1.13 g of silica sol (40% mass concentration) were stirred at room temperature for 24 hours to prepare a mixture;

[0109] The mixture was placed in a stainless steel reactor and crystallized at 180°C for 7 days. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0110] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;

[0111] SEM images of molecular sieve samples and Figure 2 Similarly, the morphology of the molecular sieve sample is a spherical aggregate morphology formed by the aggregation of nanoparticle crystals. The length of the nanoparticle crystal is 45nm, the width is 12nm, the aspect ratio is 3.8, and the size of the aggregate is 6.2μm.

[0112] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 56 by inductively coupled plasma atomic emission spectroscopy (ICP);

[0113] The total specific surface area of ​​the molecular sieve sample is 352 m 2 / g, external specific surface area 166 m 2 / g, total pore volume 0.40 cm 3 / g, micropore volume is 0.06 cm 3 / gram;

[0114] The prepared molecular sieve sample was hydrogen-modified to obtain a hydrogen-type ZSM-48 molecular sieve. The total acid content of the hydrogen-type ZSM-48 molecular sieve was 633 μmol / g, the strong acid content was 209 μmol / g, and the strong acid content accounted for 33% of the total acid content.

[0115] The hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches the highest 66%.

[0116] Example 3

[0117] 5.70 g of deionized water, 0.60 g of SDA (p is 4, q is 3, R1 and R2 are methyl, X is OH, and the average degree of polymerization is 5.2), 0.11 g of aluminum nitrate nonahydrate, 0.11 g of sodium hydroxide, and 1.80 g of tetraethyl orthosilicate were stirred at room temperature for 24 hours to prepare a mixture;

[0118] The mixture was placed in a stainless steel reactor and crystallized at 180°C for 7 days. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0119] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;

[0120] SEM images of molecular sieve samples and Figure 2 Similarly, the morphology of the molecular sieve sample is a spherical aggregate morphology formed by the aggregation of nanoparticle crystals. The length of the nanoparticle crystal is 40nm, the width is 11nm, the aspect ratio is 3.6, and the size of the aggregate is 7.0μm.

[0121] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 57 by inductively coupled plasma atomic emission spectroscopy (ICP);

[0122] The total specific surface area of ​​the molecular sieve sample is 336 m 2 / g, external specific surface area 172 m 2 / g, total pore volume 0.39 cm 3 / g, micropore volume is 0.07 cm 3 / gram;

[0123] The prepared molecular sieve sample was hydrogen-modified to obtain a hydrogen-type ZSM-48 molecular sieve. The total acid content of the hydrogen-type ZSM-48 molecular sieve was 621 μmol / g, the strong acid content was 230 μmol / g, and the strong acid content accounted for 37% of the total acid content.

[0124] The hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches a maximum of 70%.

[0125] Example 4

[0126] 6.00 g of deionized water, 0.60 g of SDA (p is 4, q is 4, R1 and R2 are methyl, X is Br, and the average degree of polymerization is 7.9), 0.08 g of aluminum nitrate nonahydrate, 0.09 g of sodium hydroxide, and 1.42 g of ethyl orthosilicate were stirred at room temperature for 24 hours to prepare a mixture;

[0127] The mixture was placed in a stainless steel reactor and crystallized at 160°C for 7 days. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0128] Figure 4 is the X-ray diffraction diagram of the molecular sieve sample, and it can be concluded that the molecular sieve sample is ZSM-48 molecular sieve;

[0129] Figure 5 and Figure 6 The SEM images of the molecular sieve sample at 10,000 times and 40,000 times respectively show that the morphology of the molecular sieve sample is a spherical agglomerate formed by the aggregation of nanoparticle crystals. The length of the nanoparticle crystal is 50nm, the width is 13nm, the aspect ratio is 3.8, and the size of the agglomerate is 4.1μm.

[0130] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 61;

[0131] The total specific surface area of ​​the molecular sieve sample is 342 m 2 / g, external specific surface area 161 m 2 / g, total pore volume 0.38 cm 3 / g, micropore volume is 0.05 cm 3 / gram;

[0132] The prepared molecular sieve sample was hydrogen-modified to obtain a hydrogen-type ZSM-48 molecular sieve. The total acid content of the hydrogen-type ZSM-48 molecular sieve was 645 μmol / g, the strong acid content was 224 μmol / g, and the strong acid content accounted for 35% of the total acid content.

[0133] The hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches the highest 64%.

[0134] Example 5

[0135] 6.90 g of deionized water, 0.36 g of SDA (p is 4, q is 4, R1 and R2 are methyl, X is Br, and the average degree of polymerization is 3.1), 0.05 g of aluminum nitrate nonahydrate, 0.12 g of sodium hydroxide, and 1.30 g of silica sol (40% mass concentration) were stirred at room temperature for 24 hours to prepare a mixture;

[0136] The mixture was placed in a stainless steel reactor and crystallized at 160°C for 7 days. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0137] X-ray diffraction patterns of molecular sieve samples and Figure 3 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;

[0138] SEM images of molecular sieve samples and Figure 4 Similarly, the morphology of the molecular sieve sample is a spherical aggregate morphology formed by the aggregation of nanoparticle crystals. The length of the nanoparticle crystal is 45nm, the width is 12nm, the aspect ratio is 3.8, and the size of the aggregate is 6μm.

[0139] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was 105 measured by inductively coupled plasma atomic emission spectroscopy (ICP);

[0140] The total specific surface area of ​​the molecular sieve sample is 319 m 2 / g, external specific surface area 178 m 2 / g, total pore volume 0.37 cm 3 / g, micropore volume is 0.06 cm 3 / gram;

[0141] The prepared molecular sieve sample was hydrogen-modified to obtain a hydrogen-type ZSM-48 molecular sieve. The total acid content of the hydrogen-type ZSM-48 molecular sieve was 357 μmol / g, the strong acid content was 123 μmol / g, and the strong acid content accounted for 34% of the total acid content.

[0142] The hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches the highest 62%.

[0143] Example 6

[0144] The method of Example 1 is followed, except that SDA (p is 4, q is 3, R1 and R2 are ethyl, X is OH, and the average degree of polymerization is 3.1) (50% mass concentration aqueous solution) is used instead of SDA (p is 4, q is 3, R1 and R2 are methyl, X is Br, and the average degree of polymerization is 3.1), and the amount of raw materials added is controlled so that the molar ratio of the final mixture is the same as that of Example 1;

[0145] The crystallization treatment was carried out at 180°C for 3 days.

[0146] Figure 7 is the X-ray diffraction diagram of the molecular sieve sample, and it can be concluded that the molecular sieve sample is ZSM-48 molecular sieve;

[0147] Figure 8 and Fig. 9 The SEM images of the molecular sieve sample at 40,000 times and 80,000 times respectively show that the morphology of the molecular sieve sample is a spherical agglomerate formed by the aggregation of nanoparticle crystals. The length of the nanoparticle crystal is 50nm, the width is 15nm, the aspect ratio is 3.3, and the size of the agglomerate is 2.8μm.

[0148] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was 116 measured by inductively coupled plasma atomic emission spectroscopy (ICP);

[0149] The total specific surface area of ​​the molecular sieve sample is 334 m 2 / g, external specific surface area 149 m 2 / g, total pore volume 0.35 cm 3 / g, micropore volume is 0.06 cm 3 / gram;

[0150] The prepared molecular sieve sample was hydrogen-modified to obtain hydrogen-type ZSM-48 molecular sieve. The total acid content of the ZSM-48 molecular sieve was 294 μmol / g, the strong acid content was 79 μmol / g, and the strong acid content accounted for 27% of the total acid content.

[0151] The hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches a maximum of 65%.

[0152] Example 7

[0153] 5.40 g of deionized water, 0.36 g of SDA (p is 4, q is 3, R1 and R2 are methyl, X is Br, and the average degree of polymerization is 3.1), 0.018 g of aluminum nitrate nonahydrate, 0.08 g of sodium hydroxide, and 0.37 g of white carbon black were stirred at room temperature for 24 hours to obtain a mixture.

[0154] The mixture was placed in a stainless steel reactor and crystallized at 170°C for 5 days. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0155] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;

[0156] SEM images of molecular sieve samples and Figure 2 Similarly, the morphology of the molecular sieve sample is a spherical aggregate morphology formed by the aggregation of nanoparticle crystals. The length of the nanoparticle crystal is 45nm, the width is 20nm, the aspect ratio is 2.3, and the size of the aggregate is 7.9μm.

[0157] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 246 by inductively coupled plasma atomic emission spectroscopy (ICP);

[0158] The total specific surface area of ​​the molecular sieve sample is 341 m 2 / g, external specific surface area 157 m 2 / g, total pore volume 0.36 cm 3 / g, micropore volume is 0.07 cm 3 / gram;

[0159] The prepared molecular sieve sample was hydrogen-modified to obtain a hydrogen-type ZSM-48 molecular sieve. The total acid content of the hydrogen-type ZSM-48 molecular sieve was 119 μmol / g, the strong acid content was 48 μmol / g, and the strong acid content accounted for 40% of the total acid content.

[0160] The hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches the highest 61%.

[0161] Example 8

[0162] 4.30 g of deionized water, 0.36 g of SDA (p is 4, q is 3, R1 and R2 are methyl, X is Br, and the average degree of polymerization is 3.1), 0.025 g of aluminum nitrate nonahydrate, 0.12 g of potassium hydroxide, and 1.27 g of ethyl orthosilicate were stirred at room temperature for 24 hours to prepare a mixture;

[0163] The mixture was placed in a stainless steel reactor and crystallized at 160°C for 9 days. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0164] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;

[0165] SEM images of molecular sieve samples and Figure 2 Similarly, the morphology of the molecular sieve sample is a spherical aggregate morphology formed by the aggregation of nanoparticle crystals. The length of the nanoparticle crystal is 45nm, the width is 22nm, the aspect ratio is 2.0, and the size of the aggregate is 3.5μm.

[0166] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured to be 191 by inductively coupled plasma atomic emission spectroscopy (ICP);

[0167] The total specific surface area of ​​the molecular sieve sample is 329 m 2 / g, external surface area 170 m 2 / g, total pore volume 0.42 cm 3 / g, micropore volume is 0.08 cm 3 / gram;

[0168] The prepared molecular sieve sample was hydrogen-modified to obtain a hydrogen-type ZSM-48 molecular sieve. The total acid content of the hydrogen-type ZSM-48 molecular sieve was 216 μmol / g, the strong acid content was 82 μmol / g, and the strong acid content accounted for 38% of the total acid content.

[0169] The hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches a maximum of 65%.

[0170] Example 9

[0171] 4.30 g of deionized water, 0.36 g of SDA (p is 4, q is 3, R1 and R2 are methyl, X is Br, and the average degree of polymerization is 3.1), 0.012 g of sodium aluminate, 0.08 g of sodium hydroxide, and 1.27 g of ethyl orthosilicate were stirred at room temperature for 24 hours to prepare a mixture;

[0172] The mixture was placed in a stainless steel reactor, heated and crystallized at 170°C for 4 days, filtered and washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0173] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-48 molecular sieve;

[0174] SEM images of molecular sieve samples and Figure 2 Similarly, the morphology of the molecular sieve sample is a spherical aggregate morphology formed by the aggregation of nanoparticle crystals. The length of the nanoparticle crystal is 50nm, the width is 18nm, the aspect ratio is 2.8, and the size of the aggregate is 6.4μm.

[0175] The SiO2 / Al2O3 molar ratio of the molecular sieve sample was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 75;

[0176] The total specific surface area of ​​the molecular sieve sample is 331 m 2 / g, external specific surface area 163 m 2 / g, total pore volume 0.40 cm3 / g, micropore volume is 0.05 cm 3 / gram;

[0177] The prepared molecular sieve sample was hydrogen-modified to obtain a hydrogen-type ZSM-48 molecular sieve. The total acid content of the hydrogen-type ZSM-48 molecular sieve was 483 μmol / g, the strong acid content was 146 μmol / g, and the strong acid content accounted for 30% of the total acid content.

[0178] The hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches the highest 66%.

[0179] Comparative Example 1

[0180] The method of Example 1 is followed, except that 1,6-hexanediamine is used as a structure directing agent (SDA), and the amount of each raw material added is controlled so that the molar ratio of the final mixture is the same as that of Example 1:

[0181] The final mixture was placed in a stainless steel reactor, heated and crystallized at 180°C for 7 days under static crystallization conditions, filtered and washed with water after the crystallization, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample; the X-ray diffraction pattern of the molecular sieve sample was similar to that of Figure 1 Similarly, it can be obtained that the molecular sieve sample is ZSM-48 molecular sieve; the SEM image of the molecular sieve sample is as follows Fig.10 As shown, it can be seen that the morphology is rod-like, not the spherical agglomerate morphology formed by the aggregation of nanoparticle crystals.

[0182] The prepared molecular sieve sample is modified into hydrogen to obtain hydrogen-type ZSM-48 molecular sieve, and the hydrogen-type ZSM-48 molecular sieve is used as a catalyst for the hydroisomerization reaction of n-heptane, and the yield of the isomer product reaches the highest 49%.

[0183] It can be seen from the results of the above examples and comparative examples that the hydrogen-type ZSM-48 molecular sieve obtained by hydrogen-modification of the ZSM-48 molecular sieve in the examples of the present invention as a catalyst for the hydroisomerization reaction of n-heptane has a good catalytic effect and can obtain a high yield of isomer products.

[0184] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A spherical ZSM-48 molecular sieve, characterized in that: The molecular sieve has a spherical aggregate morphology formed by agglomeration of nanoparticle crystals; the length of the nanoparticle crystals is 20-50nm and the width is 8-40nm.

2. The molecular sieve according to claim 1, wherein The length of the nanoparticle crystals is 25-50 nm; and / or The width of the nanoparticle crystal is 10-35 nm; and / or The size of the agglomerates is 2-10 μm, preferably 2.5-9 μm; Preferably, The aspect ratio of the nanoparticle crystals is 1.2-5, preferably 1.3-4.

5.

3. The molecular sieve according to claim 1 or 2, wherein: The total pore volume of the molecular sieve is not less than 0.2 cm 3 / g, preferably 0.2-0.6 cm 3 / g; and / or The micropore volume of the molecular sieve is not less than 0.05 cm 3 / g, preferably 0.05-0.15 cm 3 / gram.

4. The molecular sieve according to any one of claims 1 to 3, wherein The total specific surface area of ​​the molecular sieve is not less than 300 m 2 / g, preferably 300-450 m 2 / g; and / or; The external specific surface area of ​​the molecular sieve is not less than 100 m 2 / g, preferably 100-200 m 2 / g; and / or The SiO2 / Al2O3 molar ratio of the molecular sieve is 40-350, preferably 50-300.

5. A method for preparing the ZSM-48 molecular sieve according to any one of claims 1 to 4, characterized in that: The preparation method comprises: A mixed solution formed by raw materials containing silicon source, quaternary ammonium cationic polymer, alkali source and aluminum source is crystallized; Wherein, the quaternary ammonium cationic polymer is composed of the structural unit a shown in formula (I), In formula (I), p and q are each independently an integer between 2 and 4, R1 and R2 are each independently a methyl group or an ethyl group, and X is a halogen or OH.

6. The preparation method according to claim 5, wherein: The average polymerization degree of the quaternary ammonium cationic polymer is 2-20, preferably 3-13; and / or R1 and R2 are the same; Preferably, the quaternary ammonium cationic polymer is selected from one or more of the quaternary ammonium cationic polymer A1 composed of the structural unit a1, the quaternary ammonium cationic polymer A2 composed of the structural unit a2, the quaternary ammonium cationic polymer A3 composed of the structural unit a3 and the quaternary ammonium cationic polymer A4 composed of the structural unit a4, wherein: In the structural unit a1, p is 4, q is 3, R1 and R2 are methyl groups; In the structural unit a2, p is 4, q is 3, R1 and R2 are ethyl groups; In the structural unit a3, p is 4, q is 4, R1 and R2 are methyl groups; In the structural unit a4, p is 4, q is 4, and R1 and R2 are ethyl groups.

7. The preparation method according to claim 5 or 6, wherein: The silicon source is calculated as SiO2, and the quaternary ammonium cationic polymer is calculated as structural unit a, and the molar ratio of the silicon source to the quaternary ammonium cationic polymer is 1:(0.1-0.4), preferably 1:(0.1-0.35); and / or The silicon source is calculated as SiO2 and the alkali source is calculated as cations, and the molar ratio of the silicon source to the alkali source is 1:(0.15-0.5), preferably 1:(0.2-0.45); and / or The silicon source is calculated as SiO2 and the aluminum source is calculated as Al2O3, and the molar ratio of the silicon source to the aluminum source is 1:(0-0.025) and is not 0, preferably 1:(0-0.02) and is not 0; and / or The silicon source is calculated as SiO2, and the molar ratio of the silicon source to the solvent in the mixed solution is 1:(10-100), preferably 1:(12-90).

8. The preparation method according to any one of claims 5 to 7, wherein: The silicon source is selected from one or more of tetraethyl orthosilicate, fumed silica, silica sol and white carbon black; and / or The alkali source is selected from one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide; and / or The aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, sodium metaaluminate, pseudo-boehmite and aluminum isopropoxide.

9. The preparation method according to any one of claims 5 to 8, wherein: The conditions for the crystallization treatment include: The crystallization temperature is 30-190°C, preferably 140-180°C; and / or The crystallization time is 2-12 days, preferably 3-10 days; and / or, The preparation method further comprises: performing solid-liquid separation and heat treatment after crystallization treatment; Preferably, the heat treatment conditions include calcination after drying, and preferably the calcination conditions include: calcination temperature of 300-800° C.; and / or calcination time of 1-10 hours; and / or calcination in an oxygen-containing atmosphere.

10. Use of the ZSM-48 molecular sieve according to any one of claims 1 to 4 in adsorption treatment and / or organic compound conversion reaction.

11. The use according to claim 10, wherein: The ZSM-48 molecular sieve is directly used as an active component and / or the hydrogen-type ZSM-48 molecular sieve obtained by hydrogen-modification of the ZSM-48 molecular sieve is used as an active component; and / or The organic compound conversion reaction includes isomerization reaction, hydroisomerization reaction and hydrogenolysis reaction.

12. A method for the hydroisomerization of n-heptane, characterized in that: The method includes: Isomerization reaction of n-heptane in the presence of hydrogen and a catalyst containing the ZSM-48 molecular sieve according to any one of claims 1 to 4 and / or the hydrogen-type ZSM-48 molecular sieve obtained by hydrogen-modification of the ZSM-48 molecular sieve according to any one of claims 1 to 4; Preferably, the conditions for the isomerization reaction include: Mass space velocity is 0.5-3.5h -1 ; and / or The reaction temperature is 200-400°C; and / or The molar ratio of hydrogen to n-heptane is 10-40.

Citation Information

Patent Citations

  • ZSM-48 molecular sieve and preparation method thereof

    CN113548675A

  • Preparation method of hydrogen type silica-alumina ZSM-48 molecular sieve

    CN113548676A

  • Hydroisomerization catalyst and preparation method and application thereof

    CN113751060A

  • Crystalline silicate ZSM-48 and method for its preparation

    EP0142317A2